MOTIF KOMUNITAS TDA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT BLITAR - Suprianto Suprianto; Bina Andari; Ahmad Yufron (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2021)
The purpose of this research is to study and find out what motives underlie the TDA community in improving the economy of the people in Blitar. Then in the future, the results of this research are expected to provide benefits through analysis related to the motives of the TDA community in improving the economy of the people in Blitar. The research method uses descriptive qualitative research. Sources and types of data in this study by selecting one key-informant and informants on primary data, secondary data in this study are documents belonging to the Blitar TDA Community. The result of this research is that the TDA Community which is the largest community in Blitar continues to improve the economy of the Blitar community through various educational actions. These activities include holding an Entrepreneurial Party, then collaborating with campuses. The activities carried out are none other than the motive for developing the business capabilities of the Blitar community so that they can prepare accurate strategies for larger businesses which of course can improve the community's economy.